Climate Change and Human Health ECHO: Global Telementoring for Health Professionals - Joanna G Katzman (SAGE Publishing, 2021)
OBJECTIVE To increase the knowledge and communication skills of health professionals related to climate change and human health (CCHH). METHODS From February to April 2021, Project ECHO (Extension for Community Healthcare Outcomes) created an 8-week, synchronous and virtual, CCHH ECHO telementoring series for health professionals. Didactics, simulated cases, and climate change tools were used to educate the interprofessional group of participants. RESULTS During this CCHH ECHO pilot series, 625 unique participants represented 45 US states and 25 countries. The participants reported that they increased their knowledge, skills, and communication techniques regarding climate change and health. CONCLUSIONS The human health effects of climate change is an emerging field, and increasing knowledge and communication skills among health practitioners is of critical importance. The CCHH ECHO is one potential platform that may reach a diverse community of health professionals globally due to the diffusion and demonopolization of knowledge.